Exploring factors that determine effective fuel loyalty programmes in South Africa, an emerging economy - Marius Wait; Nonsikelelo Lekhuleni (Cogent Business & Management, 2020)
Loyalty programmes are not a neglected research topic. Much of this research is in the context of developed economies and within the product/service domains of marketing, and has not included loyalty programmes for fuel purchases. The purpose of this study was to determine the factors that contribute to effective loyalty programmes at fuel retailers in an emerging economy and tested an established model within this context and used literature grounding within Relationship Marketing Theory. This study used a qualitative approach and conducted nine in-depth interviews. The analyses were done using inductive content analysis. It explored areas such as the customer's view on the structure of the loyalty programme and rewards, and the customer's role in its design. Many new findings emerged, such as the participants' indifference to tier progression. The main findings indicate that theories/models developed in advanced economies do not necessarily work in emerging economies and this resulted in the construction of a new model. This study contributed to new academic knowledge within the South African context, as well as in the way that fuel loyalty programmes operate at a fundamental level and the management thereof.
Keywords: 650; fuel loyalty programmes; emerging economy; relationship marketing